Genetic analysis of reproductive and productive performance of Friesian cattle in Kenya. I. Genetic and phenotypic parameters - Rege, J.E.O. (Wiley, 1991)
An original data set of 31, 661 lactation records of Kenyan Friesian cows covering the period 1968 through 1987 was used to develop part-lactation extension factors for milk yield, and to estimate genetic parameters for production and reproductive traits. Effects of herds and year were significant for all traits studied. Season was significant for traits related to reproduction but not for production traits, although the seasonal patterns were similar in all traits. Relationship of parity with production and reproduction followed expected patterns. Adjustment factors for days in milk and for age were comparable to those developed for this breed in temperate regions, although performance level was much lower in this environment. However, heritability estimates for milk yield, age at first calving and annualized milk production were generally higher than estimates in temperate countries, and indicate high potential for improvement through selection.